Macroecology of high-elevation myxomycete assemblages in the northern Neotropics - Rojas Alvarado, Carlos Alonso (2010)
A number of recent studies have been directed towards developing a more complete understanding of myxomycete ecology throughout the world. However, the lack of comparative data obtained using standard methodologies makes the results of these studies somewhat speculative. The objective of this investigation was to examine the evidence of macroecological patterns in myxomycete assemblages in high-elevation areas of the northern Neotropics. For this, a series of study areas in Mexico, Guatemala, and Costa Rica, as well as two external study areas (one in the United States and the other in Thailand), were selected to compare the diversityenvironment relationships exhibited by myxomycetes. Altogether, the 2592 moist chamber cultures prepared yielded a total of 1377 myxomycete records, representing 89 different species. A trend of decreasing species richness with decreasing latitude was observed for the species assemblages associated with the study areas in the Neotropics. As latitude increased, species assemblages in the Neotropical study areas became increasingly similar to the temperate study area. The difference in species richness between study areas in Mexico and Thailand, along with the results obtained for a series of macroclimatic patterns evaluated in the study areas of the Neotropical region, suggests that forest structure plays an important role in the structure of myxomycete assemblages. In contrast, soil chemical characteristics and the pH of the substrates present seem to be indirectly related to the diversity estimators used for analysis, suggesting that they are probably more important at a smaller ecological scale.